Dimensional stability, mechanical and thermal performance of Flax/Carbon/Kevlar reinforced bio-phenolic/epoxy hybridcomposites - Ismail, Ahmad Safwan; Jawaid, Mohammad; Zainudin, Edi Syams; Yahaya, Ridwan; Alothman, Othman Y.; Abu-Jdayil, Basim; Sain, M. (Taylor and Francis, 2025)
This study explores the effects of hybridizing flax fabric (F) with carbon/Kevlar fabric (CK) on key material properties, including density, water absorption, void content, tensile properties, impact resistance, and thermogravimetric stability. The composites were fabricated using compression molding, employing different weight ratios of flax to carbon/Kevlar (F/CK): 100/0, 75/25, 50/50, 25/75, and 0/100, while keeping the fiber loading constant at 50 wt%. Bio-phenolic/epoxy polymer blends were used as the polymer matrix. The results indicate that as the amount of carbon/Kevlar fabric increases, the density of the hybrid composites also increases while the moisture absorption decreases. The analysis of void content in the composites suggests that the fabricated composites are well-prepared, with void content measuring less than 2%. Combining flax fiber with carbon/Kevlar fiber produces a composite with improved mechanical characteristics. Notably, the hybrid composite with a ratio of 25:75 (F: CK) demonstrated superior tensile modulus and impact strength, showing improvements of 25.96% and 16.05%, respectively, compared to the carbon/Kevlar composite. Moreover, the residue at 800°C of the composites increased with an increase in the carbon/Kevlar fabric and the highest was shown by hybrid composites with the ratio of 25:75 (F:CK), where the residue is 39.96%.